Antagonistic Effects of Sublethal Concentrations of Certain Mixtures of Metal Oxide Nanoparticles and the Bulk (Al2O3, CuO, and SiO2) on Gill Histology in Clarias gariepinus - Amaeze Henry Nnamdi; Tam-Miette Dawarri Briggs; Oluwaseun Olusola Togunde; Henry Ebele Obanya (Journal of Nanotechnology)
Background. The effect of nanoparticles (NPs) on aquatic environments is poorly studied. Aim. This study evaluates the toxicity of joint effects of these different metal nanoparticles and their bulk in mixtures (Al2O3, CuO, and SiO2) on fish using histological biomarker. Materials and Methods. The bulk and nano sizes of three salts (Al2O3, CuO, and SiO2) were used. Nanosizes ranged from 25 nm to 100 nm. The juvenile fishes of Clarias gariepinus (mean Length: 12.3 ± 3.5 cm; mean weight: 18.52 ± 6.41 g) were used for the acute and chronic toxicity tests. They were exposed to 7 mg/L each of the bulk and nano sizes of the three metallic oxides either singly or in mixtures for 28 days. The basis for the sublethal concentration was that the 96 hr acute toxicity of the varied sizes of the three metallic oxides was nontoxic up to the concentrations of 100 mg/L with no significant mortality at the highest exposure concentrations. The gills were collected for histopathology. Results. Of the three metal oxide nanoparticles, SiO was the most toxic, with histopathological alteration index (HAI) of 20.0, followed by nano-CuO (HAI, 10.0) and nano-Al2O3 (HAI, 2.0). In single exposure, the gill alterations include high frequencies of erosion of gill lamella (EGL), hypertrophy (HPT), oedema (OD), and necrosis (N). Less damage was observed at the combination of the metal oxide nanoparticles of SiO + Al2O3, SiO + CuO and SiO + Al2O3 + CuO in equal (1 : 1—HAI, 2 and 6; 1 : 1 : 1—HAI, 6) and unequal ratios (1 : 2—HAI, 16 and 6; 2 : 1—HAI, 8 and 6). Similarly, all bulk combinations were also antagonistic except for the equal ratio of bulk CuO (HAI, 20) and bulk Al2O3 (HAI, 10) that gave additive effect with HAI of 32. Conclusion. The joint actions of nano Al2O3 and CuO with SiO produced a low toxic effect, unlike the high toxicity of their single trials; this also indicates that nano Al2O3 and CuO are antagonists. Similarly, among the bulk metal oxides (SiO, Al2O3, and CuO), CuO was the most toxic. Bulk SiO and Al2O3 are antagonistic on the effects of CuO on the fish gill. There is need to properly document the ecological implications of nanoparticles in the aquatic environment.